Perancangan Sistem Kasir pada CV. Athaya menggunakan Unified Modeling Language (UML) - Michael Fernando Putra S; Siska Narulita (UNIVERSITAS STEKOM, 2024)
The utilization of information technology in the business process of a business field will be very helpful in terms of transaction processing, data processing, data analysis, and data storage. Business processes that still do not use computer technology allow many obstacles to occur, such as errors in the process of recording transactions, errors in the calculation process, difficulties in the process of storing and processing data, difficulties in making reports, and so on. CV. Athaya is a medium-scale retail business. Where currently in carrying out its transaction activities it still uses manual methods. Calculations carried out manually are of course not very effective and efficient. In addition, processes carried out manually are prone to errors in the calculation process, take a long time to complete transactions, especially if there are consumers who purchase a lot of goods, have difficulty in compiling reports, have difficulty in the process of recapitulating transaction data, are prone to losing transaction data, and various other obstacles or difficulties. Based on these problems, the research conducted has the aim of creating a cashier system design at CV. Athaya using UML diagrams. The purpose of designing this cashier system is to provide an overview of the cashier system to be built to users, namely cashiers at CV. Athaya which can simplify the ongoing transaction process, increase effectiveness and efficiency in cashier work, facilitate data processing into reports desired by business owners, minimize calculation errors, and assist in the data storage process.